Determinants of Learning Effectiveness in Digital STEM Higher Education: A Cross-Sectional Study Using Hierarchical Regression - Fresa Dwi Juniar Sofalina; Rudi Priadi; M. Iqbal Faiz (Information Technology Education Journal, 2026)
Purpose - This study examines the determinants of learning effectiveness in digital STEM higher education, focusing on Technology Integration in Management (TIM), Digital Monitoring and Evaluation (DME), and Organizational Digital Support (ODS) within an institutional context. Design - A quantitative explanatory study with a cross-sectional survey was conducted among undergraduate students (n = 260) at a private higher education institution in Bandung, Indonesia, who had experienced online or blended learning. Hierarchical multiple regression was used to assess the incremental explanatory power of TIM, DME, and ODS beyond control variables (gender, study year/semester, LMS usage intensity, and internet stability). Findings - The control model explained 14% of the variance in learning effectiveness (R² = 0.14). After including TIM, DME, and ODS, the explained variance increased to 54% (R² = 0.54; ΔR² = 0.40). DME was the strongest predictor (β = 0.33), followed by TIM (β = 0.24) and ODS (β = 0.18), all of which showed significant positive effects. The results highlight the critical role of structured monitoring, continuous evaluation, and coherent management of digital learning processes in enhancing student performance. Research implications - Enhancing digital learning effectiveness requires strengthening data-informed monitoring systems, structured LMS-based learning management, and consistent institutional support. However, the findings are limited to a single institutional context and cross-sectional design; future studies should use longitudinal and multi-institutional data. Originality/value - This study integrates technology management, evaluation practices, and organizational support into a unified digital learning governance model, providing context-specific empirical evidence from Indonesian higher education.